Analysis of the Effect of Social Media Marketing and Customer Experience on Brand Trust at Pastry XYZ - Suwarno Suwarno; Muhammad Arriansjah Rishad (Journal of Social Research, 2025)
In the digital era, social media has transformed marketing strategies, particularly for MSMEs in the competitive culinary industry. This study aims to analyze the effect of social media marketing and customer experience on brand trust at Pastry XYZ. Using a quantitative approach, data were collected through online surveys from 75 Instagram followers of Pastry XYZ selected through purposive sampling. The data were analyzed using SmartPLS 4.0 with structural equation modeling. The results show that social media marketing has a significant positive effect on brand trust (path coefficient = 0.539, p = 0.000), while customer experience does not significantly affect brand trust (path coefficient = 0.162, p = 0.209). These findings indicate that Instagram-based marketing activities effectively build consumer trust, whereas the current customer experience requires improvement to contribute meaningfully to brand trust development. The study provides practical implications for optimizing social media marketing strategies in the culinary MSME sector. In conclusion, Instagram-based marketing proves to be an effective strategy for building brand trust, whereas customer experience elements require substantial improvement to contribute to trust building.